The Aggregation of αB-Crystallin under Crowding Conditions Is Prevented by αA-Crystallin: Implications for α-Crystallin Stability and Lens Transparency. Issue 20 (18th September 2020) - Grosas, Aidan B.; Rekas, Agata; Mata, Jitendra P.; Thorn, David C.; Carver, John A.
Abstract: One of the most crowded biological environments is the eye lens which contains a high concentration of crystallin proteins. The molecular chaperones αB-crystallin (αBc) with its lens partner αA-crystallin (αAc) prevent deleterious crystallin aggregation and cataract formation. However, some forms of cataract are associated with structural alteration and dysfunction of αBc. While many studies have investigated the structure and function of αBc under dilute in vitro conditions, the effect of crowding on these aspects is not well understood despite its in vivo relevance. The structure and chaperone ability of αBc under conditions that mimic the crowded lens environment were investigated using the polysaccharide Ficoll 400 and bovine γ-crystallin as crowding agents and a variety of biophysical methods, principally contrast variation small-angle neutron scattering. Under crowding conditions, αBc unfolds, increases its size/oligomeric state, decreases its thermal stability and chaperone ability, and forms kinetically distinct amorphous and fibrillar aggregates. However, the presence of αAc stabilizes αBc against aggregation. These observations provide a rationale, at the molecular level, for the aggregation of αBc in the crowded lens, a process that exhibits structural and functional similarities to the aggregation of cataract-associated αBc mutants R120G and D109A under dilute conditions. Strategies that maintain or restore αBc stability, as αAc does, may provide therapeutic avenues for the treatment of cataract. Graphical Abstract: Unlabelled Image